128CAN ANTEGRADE AND RETROGRADE PERFUSION AND EARLY ORGAN PERFUSION DECREASE MORTALITY FROM ACUTE TYPE A AORTIC DISSECTION ASSOCIATED WITH MALPERFUSION?. (October 2014) - Imoto, K.; Uchida, K.; Karube, N.; Yasuda, S.; Isoda, S.; Suzuki, S.; Masuda, M.; Oba, M.
Abstract : Objectives: To study the effects of combined antegrade/retrograde perfusion and early organ perfusion on survival after surgery for acute type A aortic dissection with malperfusion. Methods: We studied 560 patients with acute type A aortic dissection who underwent aortic repair from November 1994 through December 2013. Until September 2005 (former period), retrograde extracorporeal circulation was performed via the femoral artery. Since October 2005 (latter period), antegrade/retrograde perfusion was performed via the subclavian and femoral arteries. Malperfusion occurred in 24% (74/303) of patients during the former period and 31% (79/257) during the latter. Among patients with myocardial ischaemia, coronary stents were placed preoperatively in 17% (4/23) during the former period and 21% (4/19) during the latter. Among patients with mesenteric ischaemia, superior mesenteric artery perfusion was performed before aortic repair in 31% (4/13) during the latter period. Among patients with limb ischaemia, lower-extremity perfusion was preoperatively performed via a temporary brachial artery-femoral artery bypass using catheters in 15% (6/40) during the latter period. In-hospital mortality was compared between the former and latter periods using Fisher's exact test. Results: In-hospital mortality did not differ between the former and latter periods in patients with non-malperfusion, but was significantly lower during the latter period in patients with malperfusion (Table 1 ). Conclusion: Antegrade plus retrograde perfusion during extracorporeal circulation combined with early organ perfusion before aortic repair can reduce in-hospital mortality in patients undergoing surgery for acute type A aortic dissection with malperfusion.